Unravelling the complexity of supply chain volatility management - Benjamin Nitsche (Logistics, 2018)
Managing supply chain volatility (SCV) is often identified as one of the major challenges of modern supply chain management. While research has predominantly focused on describing the multidimensional areas of SCV and its negative impacts, clear guidelines on how to manage SCV for efficiency, and prioritize the areas on which to focus, are sparse. This study seeks to fill this gap in the research by: (1) assessing the relative impact of SCV sources, and (2) proposing means to deal with them. Based on an Analytical Hierarchy Process conducted with 17 SCM practitioners, the paper assesses the relative impact of sources of SCV, and further contextualizes them according to factors such as product lead time and production strategy, providing more fine-grained insights for SC managers seeking to manage SCV. Subsequently, the paper applies the Nominal Group Technique with the same group of practitioners in order to identify and condense strategies for dealing with the most impactful sources of SCV (intra-organizational misalignment, inaccurate forecasting, long lead times, erratic behavior of decision makers in the supply chain, erratic behavior of customers, and high level of competition), leading to a set of 44 SCV-management strategies.
Keywords: 650; supply chain volatility; Analytical Hierarchy Process; Nominal Group Technique